Penerapan Metode Goal Programming Non-Preemptive dalam Mengoptimalkan Produksi Air Bersih PDAM Kota Padang Panjang - Safitri, Reza Dwi; Winanda, Rara Sandhy (Journal of Mathematics UNP, 2024)
The Regional Water Supply Company of Padang Panjang is a water supply company located in the city of Padang Panjang. This company has production constraints on the amount of water that does not meet the demand for clean water by customers and the operational costs of maintaining water sources are higher during the dry season than the selling price of water to customers, which causes the company to suffer losses. The purpose of this study is to optimize the production of clean water and minimize losses at the Regional Water Supply Company of Padang Panjang. The method used in this study is Non-Preemptive Goal Programming. The results of this study found a decrease in losses at the Regional Water Supply Company of Padang Panjang, which previously amounted to IDR 174,566,828 to no longer experience losses.